UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOPERATIF TIPE MAKE A MATCH - ., Thoibah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Achieving learning objectives Mathematics requires a process, namely the existence of a learning process. The learning process contains a series of actions by teachers and students on the basis of reciprocal relationships that take place in teaching situations to achieve goals. In class I at Paya Bili I Elementary School, students generally experience difficulties when asked to do the questions on the board. Even though these students actually have the ability. Real evidence that these children have the ability can be seen when they play outside the classroom. There they made scribbles on the ground and on the wall. This shows that they have the ability. To overcome the problem above, the step that needs to be implemented is to use the learning model make a macth. In its application the researchers tried on Mathematics subjects. The researcher hopes that this research will also have an impact on other subjects and be able to improve behavior in the daily lives of students in counting to hundreds. The subjects in this study consisted of 23 students, 9 men and 14 women. To achieve the results in accordance with what the researcher expects, the researchers implement them with II (two) cycles. Each cycle is 2 (two) meetings for approximately 4 (four) months. The results of the description analysis revealed, in the first cycle the average value of students amounted to 71.30 and learning completeness reached 73.90% while in the second cycle the average score of students increased to 82.17 and learning completeness reached 91.30%. The conclusion of this study is that through the use of a learning model make a macth can improve mathematics learning outcomes for class II students in semester II at Paya Bili I Elementary School 2017-2018 Academic Year.